Birth and Sathi Rites of Rana Tharus - K. C., Ganga (Cognition, 2019)
This paper shows that the animistic beliefs and practices make the Rana Tharus enthusiastic and resilient to antagonistic forces of nature. The rites of passage of Rana Tharu are occasions of community participation and reciprocity that help in maintaining their social order and social solidarity. The Rana Tharu is one of the aboriginal tribes of far-western Nepal, which falls under the Mongolian race. The population of this tribe is concentrated in the far western Terai region of Nepal, mainly in Kailali and Kanchanpur district, which is also their homeland. This research aims to portray the traditional ethnic practices of Rana Tharu with the focus on the purifying rituals of birth and Sathi that is performed after the umbilical cord drops off from the baby, which is then followed by name giving ceremony with various ceremonies offering ritual feast.The paper explores the necessary elements, ritual meanings and processes of each of these rituals.